1995
DOI: 10.1111/j.2042-3306.1995.tb04883.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of head position on upper airway function in exercising horses

Abstract: Summary The objective of the present study was to determine the effect of head and neck position on upper airway flow mechanics in exercising horses. Five Standardbred horses (452 ± 16.5 kg bwt; 4.7 ± 0.9 years [mean ± s.e.]) were exercised at 75% (Period A) and at 100% of maximal heart rate (Period B) with head and neck unrestrained, extended, or flexed. Airflow was measured using a facemask mounted pneumotachograph, while tracheal pressure during inhalation and exhalation (PUI and PUE) was measured using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 13 publications
2
71
1
2
Order By: Relevance
“…In the extreme example of the hyperflexion of the Rollkur position the cross-sectional area of the laryngeal opening is also significantly reduced [59,60]. As expected, both such reductions disproportionately increase inspiratory airflow resistance [19,48,51,52,61]. …”
Section: Some Key Attributes Of Breathing-related Functions In Thementioning
confidence: 90%
“…In the extreme example of the hyperflexion of the Rollkur position the cross-sectional area of the laryngeal opening is also significantly reduced [59,60]. As expected, both such reductions disproportionately increase inspiratory airflow resistance [19,48,51,52,61]. …”
Section: Some Key Attributes Of Breathing-related Functions In Thementioning
confidence: 90%
“…Thus, the head and neck position in horses affects upper airway flow mechanics [2,9]. Decreasing the pharyngeal diameter leads to increased resistance in respiratory airflow.…”
Section: Discussionmentioning
confidence: 99%
“…Petsche et al (1995) have scientifically demonstrated that poll flexion causes upper respiratory tract obstruction in seemingly normal Standardbred horses.…”
Section: Discussionmentioning
confidence: 99%